Salt-tolerant and thermostable mechanisms of an endoglucanase from marine Aspergillus niger - Li-Nian Cai; Sheng-Nan Xu; Tao Lu; Dong-Qiang Lin; Shan-Jing Yao (Bioresources and Bioprocessing, 2022)
Abstract The cellulase cocktail of marine Aspergillus niger exhibited salt-tolerant and thermostable properties, which is of great potential in industrial application. In order to excavate the single tolerant cellulase components from complex cellulase cocktail, constitutive homologous expression was employed for direct obtainment of the endoglucanase (AnEGL). Enzymatic property study revealed that AnEGL exhibited a property of salt tolerance and a strong thermostability in high salinity environment. Significantly, its activity increased to 129% and the half-life at 65 °C increased to 27.7-fold with the presence of 4.5 M NaCl. Molecular dynamics simulation revealed that Na+ and Cl− could form salt bridges with charged residues, and then influenced the activity of loops and the stability of substrate binding pocket, which accounted for the salt tolerance and thermostability. Further, site-specific mutagenesis study proved that the residues Asp95 and Asp99 in the pocket were of great concern for the tolerant properties. The salt-tolerant and thermostable AnEGL was of great value in lignocellulosic utilization and the conjectural mechanisms were of referential significance for other tolerant enzymes. Graphical Abstract